Duty For Acquisition of Land And Building Rights In The Implementation of Complete Systemic Land Registration In Purbalingga Regency - Denta Chanda Karita (Faculty of Law Universitas Muhammadiyah Purwokerto, 2022)
Abstract Systematic Land Registration is the process of land registration being carried out simultaneously and covering all land for the first time. Registration objects that have not been registered in a village or sub-district area or equivalent to issuing a certificate of proof of land parcels. Ownership of a plot of the land. The implementation of PTSL in Purbalingga Regency has several obstacles, such as the BPHTB report, which did not report in the last three years. Policy discrepancy between the National Land Agency of Purbalingga Regency and the Regional Finance Agency of Purbalingga Regency, especially regarding the BPHTB issue, has not been resolved. This study aims to determine the implementation of the Customs on Acquisition of Rights on Land and Buildings (BPHTB) in the Complete Systematic Land Registration (PTSL), as well as the obstacles to the implementation of the Complete Systematic Land Registration (PTSL) of the Customs for the Acquisition of Rights on Land and Buildings (BPHTB) in Purbalingga Regency. The research method used is normative juridical. The data obtained from interviews, observations, and literature studies are processed qualitatively. The solution is to improve coordination between the National Land Agency and the Regional Finance Agency of Purbalingga Regency and the parties involved in implementing the PTSL program to create synchronization or harmonization between the two to meet the formal requirements for legal certainty.Keywords: Complete Systematic Land Registration, Land and Building Rights Acquisition Fees Abstrak Pendaftaran Tanah Sistematis Lengkap (PTSL) adalah proses pendaftaran tanah untuk pertama kali, yang dilakukan secara serentak dan meliputi semua obyek pendaftaran tanah yang belum didaftarkan di dalam suatu wilayah desa atau kelurahan atau yang setingkat dengan itu dengan tujuan penerbitan sertifikat pada bidang tanah sebagai tanda bukti kepemilikan atas suatu bidang tanah. Pelaksanaan PTSL di Kabupaten Purbalingga dalam implementasinya terdapat beberapa kendala seperti belum terlapornya laporan BPHTB sejak tiga tahun terakhir dan ketidaksinkronan kebijakan antara pihak Badan Pertanahan Nasional Kabupaten Purbalingga dengan pihak Badan Keuangan Daerah Kabupaten Purbalingga khususnya terkait dengan permasalahan BPHTB yang sampai saat ini belum ada penyelesaiannya. Penelitian ini bertujuan untuk mengetahui pelaksanaan Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) dalam Pendaftaran Tanah Sistematis Lengkap (PTSL), serta kendala pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) terhadap Bea Perolehan Hak atas Tanah dan Bangunan (BPHTB) di Kabupaten Purbalingga. Metode penelitian yang digunakan adalah yuridis normatif, data yang diperoleh dari wawancara, observasi dan studi kepustakan kemudian diolah secara kualitatif. Solusi yang dapat terapkan ialah dengan meningkatkan koordinasi antara Badan Pertanahan Nasional dan Badan Keuangan Daerah Kabupaten Purbalingga serta pihak-pihak yang terlibat dalam implementasi program PTSL agar terciptanya sinkronisasi atau harmonisasi antara keduanya supaya memenuhi syarat formal kepastian hukum. Kata Kunci : Pendaftaran Tanah Sistematis Lengkap, Bea Perolehan Hak atas Tanah dan Bangunan